Application of novel non-invasive ophthalmic imaging to visualize peripapillary wrinkles, retinal folds and peripapillary hyperreflective ovoid mass-like structures associated with elevated intracranial pressure - Graven-Nielsen, Michaela; Dubra, Alfredo; Dodd, Robert L.; Hamann, Steffen; Moss, Heather E. (Frontiers in Neurology, 2024)
Elevated intracranial pressure (ICP) is a serious and potentially life-threatening condition, for which clinically useful non-invasive measures have been elusive, in some cases due to their inadequate sensitivity and specificity. Our aim was to evaluate novel non-invasive ophthalmic imaging of selected pathological features seen in elevated ICP, namely peripapillary hyperreflective ovoid mass-like structures (PHOMS), peripapillary wrinkles (PPW) and retinal folds (RF) as potential biomarkers of elevated ICP. Methods: This single-center pilot study included subjects with untreated or incompletely treated high ICP. The retinas of these subjects were evaluated with averaged en-face optical coherence tomography (OCT), OCT retinal cross-sections (OCT B-scans), adaptive optics scanning light ophthalmoscopy (AOSLO), and fundus photos.Seven subjects were included in the study. 6 subjects with high ICP (5 idiopathic intracranial hypertension, 1 medication induced, 30.8 ± 8.6 years, 75% female, 5 with papilledema) and 1 control (20-25 years) were included. PHOMS, PPW and RF were present in all subjects with papilledema, but neither in the high ICP subject without papilledema nor in the control subject. Averaged en-face OCT scans and AOSLO were more sensitive for PPW and RF than OCT Bscans and commercial fundus photos.PPW, RF and PHOMS volume have potential as non-invasive biomarkers of ICP. Novel imaging modalities may improve sensitivity. However, lack of automated image acquisition and processing limits current widespread adoption in clinical settings. Further research is needed to validate these structures as biomarkers for elevated ICP and improve clinical utility.